Data Release: DNA Barcodes of Plant Species Collected for the Global Genome Initiative for Gardens (GGI-Gardens) II - Morgan R. Gostel; Mónica M. Carlsen; Amanda Devine; Katharine B. Barker; Jonathan A. Coddington; Julia Steier (Diversity, 2022)
The Global Genome Initiative for Gardens (GGI-Gardens) is an international partnership of botanic gardens and arboreta that aims to preserve and understand the genomic diversity of plants on Earth. GGI-Gardens has organized a collection program focused on the living collections that partner institutions and supports the preservation of herbarium and genomic vouchers. Collections made through GGI-Gardens are deposited in recognized herbaria and Global Genome Biodiversity Network-partnered biorepositories worldwide, meaning that they are made available to the public. With support from its parent organization, the Global Genome Initiative (GGI), plant DNA barcode sequencing is performed using tissues collected through this partnership that represent taxa without barcode sequences in GenBank. This is the second data release published by GGI-Gardens and constitutes 2722 barcode sequences from 174 families and 702 genera of land plants. All DNA barcodes generated in this study are now available through the Barcode of Life Data Systems (BOLD) and GenBank.